The effect of lubricant viscosity on the performance of full ceramic ball bearings - Jian Sun; Jiaxing Yang; Jinmei Yao; Junxing Tian; Zhongxian Xia; Haipeng Yan; Longfei Gao; Songhua Li; Zhigang Bao (Materials Research Express, 2022)
As a new high-end bearing product, full ceramic ball bearings are favoured in a variety. However, there have been few studies on the lubrication of full ceramic ball bearings. The purpose of this study is to reveal the relationship between the vibration and temperature rise of full ceramic angular contact ball bearings and the lubricant viscosity, and to improve the service life of the bearings. In this study, the effects of lubricant viscosity on the vibration and temperature rise of silicon nitride full ceramic angular contact ball bearings under different axial loads and rotation speeds were tested. Herein, a mathematical model of oil lubrication suitable for full ceramic ball bearings is established and the relationship between the lubricant viscosity, lubricant film thickness, outer ring vibration and temperature rise of the bearing is analyzed. It was found that the vibration and temperature rise first decrease and then increase with the increase of lubricant viscosity. In this range, there is an optimal viscosity value to minimize the vibration and temperature rise of the full ceramic angular contact ball bearing. The contact surface wear of the full ceramic angular contact ball bearing varies greatly under different lubricant viscosities. There is no obvious wear on the contact surface under optimal viscosity, and the service life of the bearing is greatly improved. These results can play an important role in revealing the lubricant mechanism of full ceramic ball bearings and improving their service life under optimal lubrication.